Obesity and Osteoarthritis in Libya: Epidemiological Trends and Management Implications - Manal Abuagela,; Khawla Mshireb,; Fatima Gwili,; Marwa Altwiri,; Rehab Almertah,; Asma Alraes,; Nagat Alshohubi,; Hager Abugrain,; Shames Abuhalala, (AlQalam Journal of Medical and Applied Sciences, 2025)
Osteoarthritis (OA) is the most widespread chronic arthritis that affects the quality of a person’s life by affecting health parameters. It occurs to old people, but it can happen to adults of any age. Obesity exerts a primary influence on the musculoskeletal system, notably contributing to the development and progression of a debilitating degenerative joint disease characterized by pain, reduced mobility, and diminished quality of life. The pathogenesis of OA involves increased joint stress, changed biomechanical patterns, cytokine dysregulation, and hormonal imbalances. Obesity is suggested to be linked to a higher incidence and development of OA in both weight-bearing and non-weight-bearing joints, along with increased rates of joint replacement surgeries and related complications. In Libya, with 66.8% of adults classified as overweight and 36.2% obese, a significant portion of the population over 40 (29168 people) suffers from OA. Adopting a healthy diet, maintaining an active lifestyle, and achieving weight loss in affected individuals have been demonstrated to improve symptoms and decelerate joint deterioration. This review synthesizes data from 20-year studies, showing that obesity is a major cause of OA. The findings underscore the importance of obesity management in preventing and mitigating OA. Further research, especially in Libya, is necessary to explain the relative contributions of mechanical and metabolic factors in OA pathogenesis.